Effect of irrigation and potash levels on growth and yield of potato - Adhikari, R.C.; Rana, M.K. (Journal of Agriculture and Environment, 2018)
The experiment comprising four levels of irrigation (25, 30, 35 and 40 mm CPE) and four levels of potash (0, 100, 125 and 150 kg/ha) was conducted in Haryana Agricultural University, Hisar during winter season of 2010- 11 and 2011-12 to find out the optimum level of irrigation and potash for better growth and yield of potato. The potato variety used for the investigation was Kufri Bahar. The treatments were laid out in a split plot design with three replications keeping a net plot size of 3.6x3.6 m. The plant height at 45, 60, 75 and 90 days after planting, number of leaves per stem, leaves weight per hill, stem weight per hill, leaf area index and total and marketable tuber yield were significantly high with irrigation level 35 mm CPE and potash @ 150 kg/ha. The two years results suggest that the irrigation level 35 mm CPE in combination with potash @ 150 kg/ha has shown the best treatment combination for potato production under semiarid conditions of Hisar (Haryna).